Teachers' Efficacy of Social Modeling to Enhance Experience of Employing Interactive Whiteboards in High Schools - Mokoena, M. M.; Simelane - Mnisi, S.; Mji, A. (International Conference on Public Administration and Development Alternatives (IPADA), 2021)
This paper reports on teachers' use of role modelling in the use of the interactive whiteboards (IWB) in high schools. The Gauteng Department of Basic Education initiative of the paperless classroom whereby IWBs and tablets were utilised in public schools motivated the study. Bandura's theory of social modelling was selected to investigate how teachers could model good traits and practices in the use of IWBs in teaching and learning. Social learning theory revealed that we learn to mimic others by studying their behaviour, and we learn to behave in specific ways by watching others do what they do. The research has not come across studies that investigated the teachers' self-efficacy in social modeling in the use of the IWB. This paper will fill a gap in the literature in this area. Participants were teachers from 41 high schools in Tshwane North District, Gauteng, South Africa. This paper adopted a mixed method approach. Quantitative data were collected using Bandura's adapted self-efficacy instrument with the focus on the efficacy to make use of social models construct. Qualitative data were collected through semi-structured interview questions. Quantitative data were analysed using SPSS frequency distributions and percentages. Qualitative data were analysed with the aid of Atlas.ti. The results show that 71.5% teachers reported that they did not liaise with local institutions to assist them with the integration of ICT in teaching and learning. It was found that teachers consulted school-based information technologist personnel and fellow teachers to assist with the IWB, while on the other hand teachers indicated that they did not consult or have a mentor to assist with the integration of the IWB. It is recommended that schools should have information technology specialists to support teachers. Teachers should collaborate with nearby tertiary institutions to improve digital skills.
Journal articles published in the 6th International Conference on Public Administration and Development Alternatives (IPADA), 06-08 October 2021, Virtual Conference.
Keywords: Behaviour; UCTD; Efficacy of social modelling; Interactive whiteboards; High school